Pusat Penelitian dan Pengembangan Sosial Ekonomi Pertanian, Bogor - SRI WAHYUNI (SOCA: Jurnal Sosial Ekonomi Pertanian)
This paper describes approaches in providing a chance to people to participate in theagricultural development. The paper consist of four steps namely:1) Introduction activitiesthat should be carried out before implementing the PRA. such as recognizing each otherbetween field staffs and farmers and socialization of the program. 2) Steps and theprinciples of PRA. 3) . Increasing the participation of people throught structural approachesand 4) Increasing the participation of people through structural approaches. It is concludedthat to increase the agricultural development , the implementation of PRA is definitelyneeded. There are three steps and 20 principles of PRA method that should be followed inimplementing PRA. Before implementing PRA, recognition and program socialization areneeded. In order to get success program, a manual of the program should be prepared. Thesteps and principles of the PRA should be implemented based on the specific location. Toincrease the development of agriculture, field staffs should be understand well about thestructure and culture of the target village.ngembangan Sosial Ekonomi Pertanian, Bogor